The incidence of tuberculosis in the inflammatory bowel disease registry in Cape Town, South Africa - Pema, Mitesh Kanthi (Department of Medicine, 2022)
Background/Objectives: The risk of tuberculosis (TB) in inflammatory bowel disease (IBD) patients using immunosuppressive therapy (IST) is higher than the background population in developed countries. Corresponding data in areas of high endemicity like South Africa (SA) is limited. Our objectives were to calculate the incidence, identify predictors and determine clinical characteristics of TB common to IBD patients living in this environment. Methods: In this retrospective study, patients that developed active TB after their IBD diagnosis between 1948 and 2017 were selected from the SA IBD Registry. Incidence rates were calculated for the study population and for cases prescribed TNF-a (tumour necrosis factor-alpha) blockers. A multivariable logistic regression model, using non-TB IBD patients as controls, was applied to determine risk factors for infection. We analysed IBD and TB clinical features as well as screening tests for latent TB (LTB). Results: 42 TB cases (4%) out of 1041 consented IBD patients were identified. Incidence rates (IRs) for active infection per 100 000 person years (PY) of follow-up were 330 and 2749, for the cohort and TNF-a blocker users respectively. Patients with Crohn's disease (CD) (adjusted Odds Ratio (aOR) = 2.00, 95% confidence interval (CI): 0.92- 4.36), a smoking history (aOR = 1.44, 95% CI: 0.66-3.14), attendance at public hospitals (aOR = 1.81, 95% CI: 0.75-4.37) and a history of TNF-a blocker use (aOR = 2.45, 95% CI: 0.88- 6.80) were at greater risk for infection, although none were statistically significant. The median time to TB diagnosis was 96.7 months (interquartile range (IQR): 42.2-164.8) for the cohort and 11.3 months (IQR: 8.1-29.2) for biologics users. Over half the TB cases occurred in patients that live in districts with predominantly low-income households. The lung was the most common site affected. Latent TB infection (LTBI) occurred in twenty-four patients that were prescribed IST. Ten received isoniazid prophylaxis therapy (IPT) and one later developed active TB. Conclusion: TB is a significant problem in our IBD population. The establishment of local guidelines is recommended to assist clinicians with risk stratification and management of latent and active disease, especially in patients being considered for TNF-a blockers.